Spatial variation of beetles (Coleoptera) along an urban-rural gradient in the city of Skopje and its surrounding - Prelik, Dana; Gjorgievska, Aleksandra; Hristovski, Slavčo (Macedonian Journal of Ecology and Environment, 2009)
The aim of this investigation is to determine the impact of urbanization on beetles (Coleoptera) in three different localities (urban -U, suburban -S and rural-R) along an urban-rural gradient in the city of Skopje and its surrounding, as well as to determine the structure of the community. The material was collected monthly, during one year period (07.2004–07.2005), by using pitfall traps placed along transect. Qualitative and quantitative composition as well as seasonal dynamics and spatial variation along the gradient were determined. The presence of fifteen families was registered: Staphylinidae, Tenebrionidae, Carabidae, Curculionidae, Dermestidae, Cantharidae, Chrysomelidae, Coccinelidae, Elateridae, Histeridae, Scarabaeidae, Silphidae, Anthicidae, Lucanidae, Cerambicidae. In total, 9.14 ind./trap were found, from which the most abundant were Carabidae (3.03 ind./trap). Variations of the abundance between different families were noted during the investigation, with highest values in spring-summer period and the lowest in the winter period. Compared by localities, the abundance did not differ significantly, although the suburban locality had the lowest number of individuals.